PERENCANAAN PARTISIPATIF DENGAN PENDEKATAN FENOMENOLOGI DI DISTRIK KOMBUT KABUPATEN BOVEN DIGOEL - Arius Kambu (Universitas Cenderawasih, 2017)
This study aims to describe and analyze participatory planning processes as well as describe the representation of all stakeholders in participatory planning in Kombut District of Boven Digoel Regency. This research is a qualitative research with phenomenology approach and data collection technique done by field observation, interview, document review and literature review and empirical study. Informants in this study are village officials and community leaders. Research findings related to participatory planning revealed that the implementation of village-level development planning more done in formalities and not all stakeholder components are fully involved in the implementation of village level meetings and still found the government dominance in setting the program. While other findings related to participatory planning in community infrastructure development participate because there is income or wages earned to look reasonable but also at the same time apprehensive, on the other hand the government is considered failed in increasing community participation. Here, positive findings of participation can be said either that the community has been sensitive to the phenomenon and the reality that is happening around them, and even has provided input to the government for it. Keywords: Participatory Planning